Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð³Ð¾ Ð»ÐµÐ¹ÐºÐ¾ÐºÐ¾Ð½Ñ†ÐµÐ½Ñ‚Ñ€Ð°Ñ‚Ð° ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð½Ð° Ð²Ñ‹Ñ€Ð°Ð¶ÐµÐ½Ð½Ð¾ÑÑ‚ÑŒ ÑÐ½Ð´Ð¾Ð³ÐµÐ½Ð½Ð¾Ð¹ Ð¸Ð½Ñ‚Ð¾ÐºÑÐ¸ÐºÐ°Ñ†Ð¸Ð¸ Ð¿Ñ€Ð¸ Ð¾ÑÑ‚Ñ€Ð¾Ð¼ Ð³Ð½Ð¾Ð¹Ð½Ð¾Ð¼ Ð¿ÐµÑ€Ð¸Ñ‚Ð¾Ð½Ð¸Ñ‚Ðµ - Goltsev, K. A.; Babinets, O. M.; Kozhina, O. Yu.; Ostankova, L. V.; Goltsev, A. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
At experimental acute purulent peritonitis in animals the relaparotomy, combined injection of ampicillin and cryopreserved cord lood leucoconcentrate has been shown to provide eradication of blood from microorganisms, manifested reduction of colonization of mall intes-tine and infection of abdominal cavity with pathogenic and opportunistic bacteria, decrease in dystrophic and necrotic rocesses in abdominal cavity.